ANALYZING THE STRUCTURE AND EFFECTIVENESS OF LESSON PLANS FOR PRE-SERVICE ENGLISH LANGUAGE TEACHERS - FaqeAbdulla, Baraat Ismael (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
Planning is required for a successful teaching-learning process. It is like a series of related activitiesthat scaffold the learner because each step depends on the one before it. Therefore, it is believed thatraising effective teachers requires developing their planning skills. The goal of this study is to assessthe effectiveness of lesson plans developed by English language student-teachers at SalahaddinUniversity's College of Education. The written lesson plans that the preservice teachers submittedwere assessed using a checklist made up of the essential elements of good lesson planning. Thesample included 40 lesson plans that were created by preservice teachers. The chosen lesson planswere examined using quantitative content analysis, mainly descriptive statistics, to find out themean, median, and standard deviation. The findings imply that better guidance and instruction maybe needed for preservice teachers to effectively plan lessons. To write better lesson plans, pre-serviceteachers need teacher training programs. The research's conclusions showed that pre-serviceteachers are aware of the significance of lesson planning, but they encountered some challengeswhile doing so. As a result, creating a lesson plan became difficult. Further research will also enableus to learn more about how we can support the effective lesson-planning abilities of our futureteachers.